Barakat Syndrome: A Case Report - Ferdoush, Najia; Mutanabbi, Mahbub; Talukder, Manik Kumar; Helal, Md Al; Kawser, Choudhury Ali (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2015; VOL 39 (2) :108-109